Management of Asymptomatic Popliteal Artery Aneurysms - Kim, Tanner I.; Sumpio, Bauer E. (International Journal of Angiology, 2019)
Popliteal artery aneurysms (PAAs) are the most common peripheral artery aneurysms. They are frequently symptomatic and are associated with high rates of morbidity and limb loss. PAA can be treated by open or endovascular means, although there are no specified recommendations guiding treatment choice. This article delineates many of the differences between open and endovascular repair of asymptomatic PAA, and highlights several key articles comparing open and endovascular repair to guide decision making. Proper diagnosis and choice of repair can lead to good outcomes in the treatment of asymptomatic PAA.
Keywords: aneurysm; artery; endovascular procedure; ischemia; peripheral arterial disease; popliteal aneurysm; popliteal artery